1992
DOI: 10.1111/j.1365-2869.1992.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism and blood flow during sleep

Abstract: sleep/wake cycle, as sleep stages often alternate with a On the other hand, however, many problems concerning shorter time constant, with DS, in particular, normally not cerebral blood flow and metabolism remain to be solved lasting that long. A common strategy in most sleep studies (e.g. the regulation of blood flow, the nature of the has been, therefore, to correlate glucose utilization during flow-metabolism coupling, the existence of capillary measurement with the time spent in different sleep/wake recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 84 publications
1
37
0
Order By: Relevance
“…Cerebral blood flow, cerebral glucose metabolism and the average cerebral metabolic rate based on oxygen uptake are reduced in synchronized sleep, while they increase during REM sleep [14,20,24,26,42,46]. Furthermore, it has been demonstrated by MR with interleaved gradient-echo pulse sequences that the net flow of CSF through tile cerebral aqueduct is higher at night in normal volunteers [33].…”
Section: Discussionmentioning
confidence: 97%
“…Cerebral blood flow, cerebral glucose metabolism and the average cerebral metabolic rate based on oxygen uptake are reduced in synchronized sleep, while they increase during REM sleep [14,20,24,26,42,46]. Furthermore, it has been demonstrated by MR with interleaved gradient-echo pulse sequences that the net flow of CSF through tile cerebral aqueduct is higher at night in normal volunteers [33].…”
Section: Discussionmentioning
confidence: 97%
“…This long-term plastic response triggers the induction of expression of a coordinated set of genes involved in glycogen resynthesis such as the transcription factors C/EBP, and the genes encoding for the enzymes glycogen synthase and protein targeting to glycogen. mouse, rat and cat with the [ 14 C]2-deoxyglucose technique, have reported that energy metabolism exhibits a decrease during slow-wave sleep (SWS) and an increase during paradoxical sleep (PS), depending on the brain areas (for a review, see Franzini, 1992). It has also been reported that the synthesis of glycogen is increased during SWS with a 50-70% rise when compared to the preceding waking period (Karnovsky et al, 1983).…”
Section: Brain Energy Metabolism During Sleep-waking Cyclementioning
confidence: 99%
“…Most studies indicate that rates of global cerebral metabolism rate and cerebral blood flow (CBF) are similar during REM sleep and wakefulness (Buchsbaum et al 1989;Braun et al 1998;Franzini 1992;Kuboyama et al 1997;Lydic et al 1991;Madsen et al 1991;Madsen 1993;Maquet et al 1996). Nevertheless, the specific patterns of metabolic activity throughout the brain show distinctive regional differences between REM and waking conditions.…”
Section: Brief Review: Imaging Studies Of Sleepmentioning
confidence: 99%